2015
DOI: 10.1007/s10143-015-0622-6
|View full text |Cite
|
Sign up to set email alerts
|

Residual hemifacial spasm after microvascular decompression: prognostic factors with emphasis on preoperative psychological state

Abstract: Residual hemifacial spasm (HFS) after microvascular decompression (MVD) is common, and the factors associated with residual HFS are still controversial. In the present study, we analyzed the outcome of 212 patients with hemifacial spasm after a single microvascular decompression and evaluated the prognostic factors involved in residual hemifacial spasm. Based on our study, possible prognostic factors included indentation of the root exit zone (REZ), preoperative illness duration, and preoperative psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“… 11 12 13 33 This discrepancy can be attributed to the effects of various factors including age, disease duration, comorbidities, and psychologic status on surgical outcomes and complications. 9 18 Although we observed that facial palsy was delayed in the severe-spasm group, the complication rate was still low and so MVD could be an effective treatment option for patients with HFS. Since treatment modalities are selected and complications are predicted based on clinical or laboratory findings, rather than on intraoperative findings, more studies focusing on the clinical features of HFS—like the present study—are important for providing doctors with the best information possible for making appropriate decisions.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“… 11 12 13 33 This discrepancy can be attributed to the effects of various factors including age, disease duration, comorbidities, and psychologic status on surgical outcomes and complications. 9 18 Although we observed that facial palsy was delayed in the severe-spasm group, the complication rate was still low and so MVD could be an effective treatment option for patients with HFS. Since treatment modalities are selected and complications are predicted based on clinical or laboratory findings, rather than on intraoperative findings, more studies focusing on the clinical features of HFS—like the present study—are important for providing doctors with the best information possible for making appropriate decisions.…”
Section: Discussionmentioning
confidence: 80%
“…Despite the wide-ranging impact of HFS, the significance of its clinical features has not been clearly demonstrated. Only a few clinical characteristics of HFS have been reported previously and no consensus has been reached, 9 10 11 while various surgical findings including intraoperative severity of indentation or resolution of the lateral spread response were suggested to be related to surgical outcome. 10 11 12 13 It is particularly notable that the severity of HFS is a clinical barometer that can be easily assessed in a clinic, but there is no consensus on how to evaluate spasm severity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated the predicting factors influencing the outcome following MVD in HFS patients [ 6 , 17 , 18 , 23 , 39 ]. Fewer studies analyzed the course of symptoms improvement and patterns of recovery following MVD attributing delayed resolution of the spasms to various predicting factors [ 18 , 24 , 27 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small Teflon felt may drift away, and a large Teflon felt may cause a new compression; in addition, the oversized Teflon may block the surgeon's vision and the offending vessel may be overlooked. Some experts [17][18][19][20][21] have reported that a few patients with poor postoperative outcome after the initial MVD are likely to be cured in 1 to 3 years without additional operations. It is worth re-exploring if delayed resolution after 2 to 3 years could not be observed.…”
Section: Teflon Felts Affect the Outcomes Of Mvdmentioning
confidence: 99%